Equity or gap? Women in open-access Latin American communications journals indexed in Scopus - Perdomo, Bexi (2023)
The research studies the presence of female authors of scientific articles in Latin American communication journals, both in individually authored articles and collaborative works. It analyzed 206 research articles published in two open-access Latin American journals indexed in Scopus and exclusively focused on communications. The results revealed 441 authors (54 % men and 46 % women). Men had a greater presence as authors of individual articles. In articles with multiple authors, women prevail in the first authorship position (men n = 60; women n = 75) and the third position (men n = 6; women n = 8), while men prevail in the second position (men n = 70; women n = 65) and the last position (men n = 49; women n = 31). The Chi-square test (p < 0.05) showed a statistically significant association between gender and position in multiple authorships. The article concludes that, although there is a gender inequity in communication articles, the gap is smaller than reported by authors in other knowledge areas.